Nucleotide sequence homology requirements of HIV-1-specific short hairpin RNA - Pusch, Oliver (Oxford University Press, 2003)
The degradation of a selected mRNA species by RNA interference requires a high degree of homology between the short interfering or short hairpin RNA (si or shRNA) and its target. Recent reports have demonstrated that the number and location of nucleotide mismatches affect the activity of si/shRNA. Here, we systematically examined the effect of single nucleotide mutations in all 21 positions of an effective shRNA that targets the gag gene of HIV-1. We found that all mutant shRNAs exerted RNAi activity but were less effective in gene silencing compared to the wild-type gag shRNA. The most pronounced reduction in function was observed with mutations in the central and 5′ regions of the shRNA. Our results demonstrate that optimal gene silencing requires perfect homology between shRNA and the chosen target, but that a variable degree of silencing occurs, depending upon the precise location of nucleotide mismatches.